Transcript Profiles of Stria Vascularis in Models of Waardenburg Syndrome - Linjun Chen; Lin Wang; Lei Chen; Fangyuan Wang; Fei Ji; Wei Sun; Hui Zhao; Weiju Han; Shiming Yang (Neural Plasticity)
Background. Waardenburg syndrome is an uncommon genetic condition characterized by at least some degree of congenital hearing loss and pigmentation deficiencies. However, the genetic pathway affecting the development of stria vascularis is not fully illustrated. Methods. The transcript profile of stria vascularis of Waardenburg syndrome was studied using Mitf-M mutant pig and mice models. Therefore, GO analysis was performed to identify the differential gene expression caused by Mitf-M mutation. Results. There were 113 genes in tyrosine metabolism, melanin formation, and ion transportations showed significant changes in pig models and 191 genes in mice models. In addition, there were some spice’s specific gene changes in the stria vascularis in the mouse and porcine models. The expression of tight junction-associated genes, including Cadm1, Cldn11, Pcdh1, Pcdh19, and Cdh24 genes, were significantly higher in porcine models compared to mouse models. Vascular-related and ion channel-related genes in the stria vascularis were also shown significantly difference between the two species. The expression of Col2a1, Col3a1, Col11a1, and Col11a2 genes were higher, and the expression of Col8a2, Cd34, and Ncam genes were lower in the porcine models compared to mouse models. Conclusions. Our data suggests that there is a significant difference on the gene expression and function between these two models.